Cervical Pessary to Prevent Preterm Birth in Women With Twin Gestation and Sonographic Short Cervix: A Multicentre Randomized Controlled Trial (PECEP-Twins). Issue 4 (December 2016) - Goya, M.; de la Calle, M.; Pratcorona, L.; Merced, C.; Rodó, C.; Muñoz, B.; Juan, M.; Serrano, A.; Llurba, E.; Higueras, T.; Carreras, E.; Cabero, L.
Abstract : ( Am J Obstet Gynecol. 2016;214(2):145–152) The primary risk factor for perinatal morbidity and mortality is noted to be spontaneous preterm birth (SPB) and the risk increases in twin gestations. Early and very early birth among twins is attributed to mothers having short cervical length (CL). It is also seen that 15% of women with twin gestations have CL≤25 mm. This measurement has become the benchmark for identifying women at risk of preterm delivery. Vaginal progesterone, cervical cerclage, and cervical pessary are the choices available for the management of patients with short CL. Use of vaginal progesterone did not reduce the rate of preterm delivery but the rate of neonatal morbidity decreased. Adverse outcome in twin gestations has been associated with cervical cerclage. Cervical pessary—a small ring shaped device made of silicone—was introduced in 1960 as a preventive measure for short CL. This device is inserted around the cervix, and a considerable fall in the preterm birth rate was recorded after this device came in use. Although, earlier clinical trial reports showed favorable results, the evidence came from nonrandomized study designs. Thus, further evidence supporting the role of cervical pessary in reducing the preterm birth rate was sought.